Potential of aqueous extracts of Allium sativum, Mentha spicata, Myrtus communis and Thymus vulgaris as antimicrobials and curing of antibiotic resistant genes in Klebsiella pneumoniae / Adel Kamal Khider and Sazan Qadir Mawlud - Khider, Adel Kamal; Mawlud, Sazan Qadir (Universiti Teknologi MARA, Negeri Sembilan, 2012)
Eighty six clinical isolates of Klebsiella pneumoniae were isolated from various pathogenic cases from Erbil hospitals. The isolates were varied in their resistance to antibiotics, and ranged between 13-18 antibiotics out of 22. Genetic transformation between purified plasmid from K. pneumoniae and E. coli JM83 demonstrated that all tested antibiotic resistant genes were plasmid DNA born except Doxycilin resistance gene was chromosomal born. The watery extracts of Allium sativum, Mentha spicata Myrtus communis and Thymus vulgaris were proved to be most powerful against K. pneumoniae K11 and K32 isolates. A comparative evaluation of plasmids elimination from K. pneumoniae isolates by sub-MIC of plant extracts showed that these extracts could cure plasmids effectively at their respective sub-MIC concentration. Plasmid cured was observed by sub-MIC of Allium sativum and Thymus vulgaris at 350 µg ml-1 cured 2, 4 and 3 plasmids, Mentha spicata and Myrtus communis extract at 250 µg ml-1cured 2, 3 and 2, 4 plasmids from K. pneumoniae K11 and K32 isolates. Curing of plasmid DNA from K. pneumoniae isolates confirmed by determining the loss of resistance markers in cured cultures.